Utility of Pathology Imagebase for standardisation of prostate cancer grading. Issue 1 (5th March 2018) - Egevad, Lars; Delahunt, Brett; Berney, Daniel M; Bostwick, David G; Cheville, John; Comperat, Eva; Evans, Andrew J; Fine, Samson W; Grignon, David J; Humphrey, Peter A; Hörnblad, Jonas; Iczkowski, Kenneth A; et al.
Abstract : Aims: Despite efforts to standardise grading of prostate cancer, even among experts there is still a considerable variation in grading practices. In this study we describe the use of Pathology Imagebase, a novel reference image library, for setting an international standard in prostate cancer grading. Methods and results: The International Society of Urological Pathology (ISUP) recently launched a reference image database supervised by experts. A panel of 24 international experts in prostate pathology reviewed independently microphotographs of 90 cases of prostate needle biopsies with cancer. A linear weighted kappa of 0.67 (95% confidence interval = 0.62–0.72) and consensus was reached in 50 cases. The interobserver weighted kappa varied from 0.48 to 0.89. The highest level of agreement was seen for Gleason score (GS) 3 + 3 = 6 (ISUP grade 1), while higher grades and particularly GS 4 + 3 = 7 (ISUP grade 3) showed considerable disagreement. Once a two‐thirds majority was reached, images were moved automatically into a public database available for all ISUP members atwww.isupweb.org . Non‐members are able to access a limited number of cases. Conclusions: It is anticipated that the database will assist pathologists to calibrate their grading and, hence, decrease interobserver variability. It will also help to identify instances where definitions of grades need to be clarified.